2010
DOI: 10.1159/000310338
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Emergency and Final Diagnosis Coding in Transient Ischemic Attack: South Western Sydney Transient Ischemic Attack Study

Abstract: Background: It is important to establish the validity of diagnostic coding in administrative datasets used in stroke and transient ischemic attack (TIA) research. This study examines the accuracy of emergency department (ED) TIA diagnosis and final diagnostic coding after hospital admission. Methods: Using administrative datasets, we identified all patients with an ED TIA diagnosis (435.9; ICD-9) admitted to Liverpool Hospital from January 2003 to December 2007. ED and hospital admission records were matched a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 27 publications
2
32
0
Order By: Relevance
“…[23][24][25] In our study, the discharge diagnosis of TIA agreed with the diagnosis after being seen in the neurovascular clinic in 86.4% of patients. Including or excluding these patients did not change our results.…”
Section: Discussionsupporting
confidence: 73%
“…[23][24][25] In our study, the discharge diagnosis of TIA agreed with the diagnosis after being seen in the neurovascular clinic in 86.4% of patients. Including or excluding these patients did not change our results.…”
Section: Discussionsupporting
confidence: 73%
“…18 A small proportion of patients with TIA mimics are coded as TIA. 19 The DRG system has been used in previous studies pertaining to costs and length of stay of stroke patients. 20 We think that using a combination of DRG and ICD-9-CM codes would result in higher accuracy for TIA patient identification.…”
Section: Discussionmentioning
confidence: 99%
“…We present data on TIA admissions to all hospitals within the state of New South Wales (NSW), Received August 15, 2011; accepted September 9, 2011 We identified and excluded potential mimic disorders based on an Australian validation study of TIA hospital coding, which identified recognized diagnoses mistaken for TIA at presentation, including stroke, epilepsy and convulsions, migraine, traumatic brain injury, primary and secondary cerebral malignancies, syncope and collapse, toxic-metabolic disturbances, neurodegenerative conditions, and sepsis, including central nervous system infections. 21 We expected approximately 12% of identified patients with TIA to be misclassified cases. 21 Patients with a prior hospitalization for stroke were not excluded.…”
mentioning
confidence: 98%
“…21 We expected approximately 12% of identified patients with TIA to be misclassified cases. 21 Patients with a prior hospitalization for stroke were not excluded.Data linkage was performed centrally by a government and university-sponsored organization carrying out deidentified data linkage of routinely collected administrative data. 20…”
mentioning
confidence: 98%
See 1 more Smart Citation